Iñaki Abalos & Juan Herreros (A+U, 1997)
Obras y proyectos del estudio, 1989-1995: Gordillo House (1993-1995); Town Hall and Cultural Center (1993-1995); Headquarters Building. Ministry of the Interior (1991-1993); Municipal Gymnasiun (1989-1992); Public Library at Usera (1995-).